USAHA JAJANAN BALI KERING DENGAN PENERAPAN ALAT SPINER DAN SEALER DI DESA CANDI KUNING - Pudja, I.A.R.P.; Kencana, P. K. D.; Nada, I M. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
The aims of the activities of community service was to increase the economic value of Balinese snack and to implement of appropriate technology in the business development of traditional Balinese snack. The method of community service was field surveys and interviews, given the right technology equipment for business development of traditional Balinese snack, counseling and training of science and appropriate technology. Implementation of community service was to a business partner of Balinese snack have been given deep fryer of traditional Balinese snack, given sealer for plastic packaging, training for the labeling on the packaging of traditional Balinese snack, monitoring and mentoring of production. The conclusion from this community service was the implementation of activities going on smoothly and there was a two-way discussion of theactive participants with questions and responses to the topic. Activities like this was very useful for the people in the village. So,the same activities need to becarried out in other villages that have the same agricultural commodities.